Dielectric substance and laminated electronic component

A dielectric composition with optimized segregation and pore structures enhances sinterability and durability, addressing crack issues in laminated electronic components.

JP2025018133APending Publication Date: 2025-02-06TDK CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023121597
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-26
Publication Date
2025-02-06

AI Technical Summary

Technical Problem

Dielectric materials in laminated electronic components are prone to cracks and chips due to segregation and pore structures that lead to stress and poor sinterability.

Method used

A dielectric composition with a specific combination of segregation and pores, where the pore diameter is smaller than the segregation diameter, and a ratio of segregation to pore is optimized, along with a controlled linear expansion coefficient, to enhance sinterability and durability.

Benefits of technology

The dielectric composition improves sinterability, insulation resistance, and reduces crack occurrence, enabling reliable performance under various conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025018133000001_ABST
    Figure 2025018133000001_ABST
Patent Text Reader

Abstract

To provide a dielectric substance that is resistant to cracks and chips, and a laminated electronic component that includes the dielectric substance.SOLUTION: A dielectric substance includes dielectric particles, segregations, and pores. In a cross section, the dielectric substance has a special combination in which the segregations and the pores are in contact with each other.SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a dielectric and a laminated electronic component. [Background technology]

[0002] Patent Document 1 describes an invention related to a multilayer ceramic capacitor, in which a sintering aid component containing Si is segregated in voids formed in a conductor formation region. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2004-273975 A Summary of the Invention [Problem to be solved by the invention]

[0004] The present invention provides a dielectric material that is resistant to cracks and chips, and a laminated electronic component that includes the dielectric material. [Means for solving the problem]

[0005] In order to achieve the above object, the dielectric material according to the present invention comprises: Contains dielectric particles, segregations, and pores; In the cross section, there is a special combination in which the segregations and the pores are in contact with each other.

[0006] The diameter of the pores of the special combination may be smaller than the diameter of the segregation of the special combination.

[0007] The value obtained by dividing the average diameter of the segregations by the average diameter of the pores may be greater than 1.00 and equal to or less than 6.00.

[0008] The ratio of the number of the special combinations in the cross section of the dielectric is 2.0×10 4 pieces / mm 2 That's it, 5.0 x 106 pieces / mm 2 It may be the following.

[0009] The linear expansion coefficient of the segregation may be smaller than the linear expansion coefficient of the dielectric particles.

[0010] The element other than O, Ca, Sr, Zr and Ti that is contained in the segregation in the largest amount on the basis of atomic number may be Si.

[0011] The particle size of the dielectric particles may be 0.10 μm or more and 3.00 μm or less.

[0012] The dielectric particles have the composition formula [(Ca x Sr 1-x )O] n [(Ti y Zr 1-y )O2] may be included.

[0013] The dielectric particles may include barium titanate.

[0014] A laminated electronic component according to the present invention includes the above-mentioned dielectric material. [Brief description of the drawings]

[0015] [Figure 1] FIG. 1 is a schematic cross-sectional view of a multilayer ceramic capacitor. [Diagram 2] Figure 2 is a STEM-DF image of a cross section of a dielectric material. [Diagram 3] FIG. 3 is a schematic diagram of a cross section of a dielectric material. [Figure 4] FIG. 4 is a schematic diagram of a cross section of a dielectric material. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] In this embodiment, a multilayer ceramic capacitor 2 shown in Fig. 1 will be described as an example of a ceramic electronic component according to the present invention. The multilayer ceramic capacitor 2 has an element body 4 and a pair of external electrodes 6 formed on the outer surface of the element body 4.

[0017] The shape of the element body 4 shown in Fig. 1 is generally a substantially rectangular parallelepiped, and has two end faces 4a opposing each other in the X-axis direction, two side faces 4b opposing each other in the Y-axis direction, and two side faces 4b opposing each other in the Z-axis direction. There is no particular limit to the external dimensions of the element body 4. For example, the length L0 of the element body 4 in the X-axis direction may be 0.4 mm to 5.7 mm, the width W0 in the Y-axis direction may be 0.2 mm to 5.0 mm, and the height T0 in the Z-axis direction may be 0.2 mm to 3.0 mm. In this embodiment, the X-axis, Y-axis, and Z-axis are perpendicular to each other.

[0018] The element body 4 has ceramic layers 10 and internal electrode layers 12 that are substantially parallel to a plane including the X-axis and Y-axis. Inside the element body 4, the ceramic layers 10 and the internal electrode layers 12 are alternately stacked along the Z-axis direction. Here, "substantially parallel" means that most of the portions are parallel, but some portions may not be parallel. The ceramic layers 10 and the internal electrode layers 12 may be slightly uneven or inclined.

[0019] There is no particular limitation on the shape of the element body 4. In addition to the roughly rectangular parallelepiped shape shown in Fig. 1, other shapes include an elliptical cylinder, a circular cylinder, and a rectangular column.

[0020] The ceramic layers 10 are made of a dielectric material, which will be described later. There is no particular limit to the average thickness (interlayer thickness) of each ceramic layer 10. The average thickness of each ceramic layer 10 may be 100 μm or less, or may be 30 μm or less. There is no particular limit to the number of layers of the ceramic layers 10. The number of layers of the ceramic layers 10 may be determined according to the desired characteristics. The number of layers of the ceramic layers 10 may be 20 or more, or may be 50 or more.

[0021] The internal electrode layers 12 are laminated between the ceramic layers 10. That is, the number of laminated internal electrode layers 12 is determined according to the number of laminated ceramic layers 10. There is no particular limit to the average thickness of each of the internal electrode layers 12. The average thickness of each of the internal electrode layers 12 may be 3.0 μm or less.

[0022] The average thickness of the ceramic layers 10 is calculated by observing a cross section as shown in FIG. 1 using a metallurgical microscope, measuring the thickness of each ceramic layer 10 at at least five points, and averaging the measured thicknesses.

[0023] The average thickness of the internal electrode layers 12 is calculated by observing a cross section as shown in FIG. 1 using a metallurgical microscope, measuring the thickness of each internal electrode layer 12 at at least five or more points, and averaging the measured thickness.

[0024] The internal electrode layers 12 are laminated such that one end is alternately exposed on two end faces 4a opposing each other in the X-axis direction of the element body 4. A pair of external electrodes 6 are formed on one end face 4a of the element body 4, and are electrically connected to the exposed ends of the alternately arranged internal electrode layers 12. By forming the internal electrode layers 12 and external electrodes 6 in this manner, a capacitor circuit is formed by the external electrodes 6 and the internal electrode layers 12. That is, the ceramic layers 10 present in the capacitance region are sandwiched between the internal electrode layers 12 of opposite polarity, and a voltage can be applied to the ceramic layers 10.

[0025] The internal electrode layer 12 is made of a conductive material. The internal electrode layer 12 may contain Ni as a main component. The conductive material constituting the internal electrode layer 12 may be pure Ni or a Ni-based alloy containing 85 mass% or more of Ni. The Ni-based alloy may contain one or more elements selected from Mn, Cu, Cr, etc. together with Ni. In addition to the conductive material, the internal electrode layer 12 may contain particles of a perovskite compound having the same composition as the main component of the ceramic layer 10 as a co-material. The internal electrode layer 12 may contain a small amount of non-metallic components such as S and P. For example, it may contain about 0.1 mass% or less. Furthermore, the internal electrode layer 12 may contain voids.

[0026] In addition, when a common material, a gap, or the like is contained in the internal electrode layer 12, discontinuous portions where no electrode (conductive material) is present may be formed in the internal electrode layer 12.

[0027] The pair of external electrodes 6 may include a baked electrode layer, a resin electrode layer, a plated electrode layer, etc. The pair of external electrodes 6 may be composed of a single electrode layer, or may be composed of a laminate of multiple electrode layers. For example, the external electrode 6 may have a three-layer structure of a baked electrode layer containing Cu--a Ni plating layer--a Sn plating layer (laminate in the order listed). When the external electrode 6 is formed with this three-layer structure, the Sn plating layer is located on the outermost surface of the external electrode 6, and therefore the solder wettability of the external electrode 6 is good.

[0028] 1, the external electrode 6 integrally has an end surface portion formed on the end surface 4a in the X-axis direction of the element body 4, and extended portions formed at the ends in the X-axis direction on the four side surfaces 4b of the element body 4. That is, the pair of external electrodes 6 are each formed so as to wrap around from the end surface 4a to the side surfaces 4b of the element body 4, and are insulated so as not to contact each other in the X-axis direction.

[0029] The extensions of the external electrodes 6 are not essential, and the external electrodes 6 may be composed of only the end surface portions. Alternatively, when the multilayer ceramic capacitor 2 is surface-mounted on a substrate, the extensions of the external electrodes 6 need only be formed on at least the side surface 4b facing the mounting surface of the substrate, and do not necessarily have to be formed on the side surface 4b opposite the mounting surface.

[0030] A cross-section of the ceramic layer 10 containing the above components, i.e., a cross-section of the dielectric material constituting the ceramic layer 10, is observed at a magnification of 50,000 times using a STEM, and a cross-sectional photograph is shown in Fig. 2. The dielectric material constituting the ceramic layer 10 includes dielectric particles 21, segregations 23a, 23b, and pores 25a. The segregations 23a, 23b and the pores 25a are included in the grain boundaries located between two or more dielectric particles 21. Note that an SEM or the like may be used instead of the STEM.

[0031] There is no particular limit to the method for distinguishing the dielectric particles 21, the segregations 23a and 23b, and the pores 25a. Figure 2 shows a STEM-DF image obtained by STEM. In the STEM-DF image, the dielectric particles 21 appear the brightest, and the pores 25a appear the darkest. The segregations 23a and 23b appear to be intermediate in brightness between the dielectric particles 21 and the pores 25a.

[0032] In order to more clearly distinguish the dielectric particles 21, the segregations 23a and 23b, and the pores 25a, a mapping analysis may be performed using STEM-EDS. By using a mapping image obtained by the mapping analysis in combination with a STEM-DF image, the distinction can be made more clearly. In the mapping image, a region where the abundance ratio of a specific element is high, that is, a region where a specific element is segregated, can be specified by the shade of the color tone. In an element mapping image of an element that is relatively abundant in the segregations 23a and 23b, the segregations 23a and 23b appear dark. In contrast, the pores 25a appear light in the element mapping image of any element. Note that STEM-WDS, SEM-EDX, or SEM-WDS may be used instead of STEM-EDS.

[0033] The dielectric constituting the ceramic layer 10 has a special combination in which the segregation 23a and the pores 25a are in contact with each other in the cross section. The special combination of the dielectric constituting the ceramic layer 10 tends to improve the sinterability of the dielectric. This tends to improve the insulation resistance and durability of the dielectric. In particular, the dielectric is less likely to crack.

[0034] Segregation 23b is a segregation that is not in contact with pores. Segregation 23b does not have to be included in the dielectric that constitutes ceramic layer 10. Although not shown in FIG. 2, pores that are not in contact with segregations may be included in the dielectric that constitutes ceramic layer 10.

[0035] There is no particular limit to the number ratio of the special combinations in the cross section of the dielectric material constituting the ceramic layer 10. For example, 4 pieces / mm 2 Above 1.0×10 8 pieces / mm 2 It may be less than or equal to 1.2 x 10 4 pieces / mm 2 More than 3.9 x 10 7 pieces / mm 2 It may be less than or equal to 2.0 x 10 4 pieces / mm 2 Above 5.0×10 6 pieces / mm 2 When the ratio of the number of the special combination is within the above range, the sinterability of the dielectric is easily improved, and the insulation resistance and durability of the dielectric are easily improved. In particular, the dielectric is less susceptible to cracking.

[0036] When calculating the percentage of the number of special combinations, the cross section of the dielectric material constituting the ceramic layer must be at least 1000 μm in total. 2 The above observations are made. Then, the number of special combinations present in the observed cross section is confirmed, and the ratio of the number of special combinations is calculated. 2 As described above, a plurality of observation ranges may be set for observation.

[0037] In the cross section of the dielectric, one segregation 23a may be in contact with multiple pores 25a. In that case, the number of pores 25a in contact with one segregation 23a is the number of special combinations. One pore 25a may be in contact with multiple segregations 23a. In that case, the number of segregations 23a in contact with one pore 25a is the number of special combinations.

[0038] The number of the special combination segregation 23a in the case where the pores 25a are in contact with the end on the long diameter side may be about four times or more than the number of the pores 25a in the case where the pores 25a are in contact with the end on the short diameter side. In Fig. 2, the pores 25a are in contact with the end on the long diameter side of the special combination segregation 23a.

[0039] There is no particular limit to the particle size of the dielectric particles 21. The particle size of the dielectric particles 21 may be 5.00 μm or less, or may be 0.10 μm or more and 3.00 μm or less. There is also no particular limit to the average particle size of the dielectric particles 21. The average particle size of the dielectric particles 21 may be 5.00 μm or less, or may be 0.10 μm or more and 3.00 μm or less.

[0040] The diameter of the segregations 23a, 23b is not particularly limited. The diameter of the segregations 23a, 23b may be 5.00 μm or less, or may be 0.05 μm or more and 2.00 μm or less. The average diameter of the segregations 23a, 23b is also not particularly limited. The average diameter of the segregations 23a, 23b may be 4.00 μm or less, or may be 0.04 μm or more and 1.50 μm or less.

[0041] There is no particular limitation on the diameter of the pores 25a. The diameter of the pores 25a may be 1.50 μm or less, or may be 0.01 μm or more and 0.50 μm or less. There is also no particular limitation on the average diameter of the pores 25a. The average diameter of the pores 25a may be 1.00 μm or less, or may be 0.03 μm or more and 0.45 μm or less.

[0042] The value obtained by dividing the average diameter of the segregations 23a, 23b by the average diameter of the pores 25a may be 0.19 or more and 10.40 or less, may be greater than 1.00 and 6.00 or less, or may be 1.70 or more and 5.33 or less.

[0043] In particular, when the value obtained by dividing the average diameter of the segregations 23a, 23b by the average diameter of the pores 25a is greater than 1.00 and not more than 6.00, the sinterability of the dielectric is easily improved, and the insulation resistance and durability of the dielectric are easily improved. In particular, the dielectric is less susceptible to cracking.

[0044] The minimum diameter of segregation and pores is 1.0 nm. In other words, any part with a diameter of less than 1.0 nm is not considered to be a segregation or a pore.

[0045] The particle size of the dielectric particle 21, the diameter of the segregations 23a and 23b, and the diameter of the pores 25a can be measured by image analysis of the cross-sectional photograph. There is no particular limit to the type of cross-sectional photograph. As described above, the cross-sectional photograph may be obtained using a STEM, or may be obtained using a SEM, TEM, or the like.

[0046] The particle diameter of the dielectric particle 21 is the circle-equivalent diameter of the dielectric particle 21. The diameters of the segregations 23a, 23b are the circle-equivalent diameters of the segregations 23a, 23b. The diameter of the pore 25a is the circle-equivalent diameter of the pore 25a.

[0047] The equivalent circle diameter is the diameter of a circle with the same area.

[0048] The average particle size of the dielectric particles 21 can be calculated by measuring and averaging the circle-equivalent diameters of at least five or more dielectric particles 21. The average diameter of the segregations 23a, 23b can be calculated by measuring and averaging the circle-equivalent diameters of at least five or more segregations 23a, 23b. The average diameter of the pores 25a can be calculated by measuring and averaging the circle-equivalent diameters of at least five or more pores 25a.

[0049] The diameter of the special combination segregations 23a in contact with each other and the diameter of the special combination pores 25a in contact with the segregations 23a may be compared, and the diameter of the special combination pores 25a may be smaller than the diameter of the special combination segregations 23a.

[0050] The composition of the dielectric particles 21 is not particularly limited. The dielectric particles 21 may contain a component containing Ca, Sr, and / or Ba as a main component. The dielectric particles 21 may contain a perovskite compound represented by the general formula ABO3 as a main component. Examples of perovskite compounds include barium titanate, calcium titanate, strontium titanate, calcium zirconate, strontium zirconate, and calcium strontium zirconate. The dielectric particles 21 may contain barium titanate as a main component.

[0051] The dielectric particles 21 are mainly composed of the composition formula [(Ca x Sr 1-x )O] n [(Ti y Zr 1-y The composition ratio is expressed based on the number of atoms.

[0052] n indicates the content ratio of A sites to B sites, and may be 1.0 or more and 1.2 or less.

[0053] x represents the content ratio of Ca in the A site, and may be 0 or more and 1 or less.

[0054] The symbol y represents the content ratio of Ti in the B site, and may be 0 or more and 0.3 or less.

[0055] The element ratio of oxygen (O) in the above composition formula may deviate slightly from the stoichiometric composition.

[0056] The main component of the dielectric particle is a component that is contained in an amount of 95 mol % or more relative to the entire dielectric particle.

[0057] The composition of the segregation is not particularly limited. The segregation may be an element other than O, Ca, Sr, Zr, and Ti that is contained most abundantly based on the atomic number, and may be Si. When the segregation contains a large amount of Si, the sinterability of the dielectric material is easily improved. And, the insulation resistance and durability of the dielectric material are easily improved.

[0058] In addition, the total area of ​​segregations in a cross section may be 100%, and the area ratio of segregations in which the element most abundant, based on atomic number, other than O, Ca, Sr, Zr, and Ti is Si may be 25% or more in total.

[0059] The segregation may contain a Ca-Sr-Mn-Si based component as a main component. The Ca-Sr-Mn-Si based component may be an oxide. The component functions as a sintering aid.

[0060] The main component of the segregation is a component that is contained in an amount of 80 mol % or more relative to the entire segregation.

[0061] The Ca-Sr-Mn-Si based component refers to a component in which the contents of Ca, Sr, Mn and Si are each 3 mol % or more, relative to 100 mol % of the total content of elements other than O.

[0062] In the Ca-Sr-Mn-Si system components, the total content of elements other than O is taken as 100 mol%, and the Ca content may be 20 mol% or more and 60 mol% or less. The Sr content may be 10 mol% or more and 30 mol% or less. The Mn content may be 3 mol% or more and 12 mol% or less. The Si content may be 15 mol% or more and 45 mol% or less.

[0063] The dielectric constituting the ceramic layer 10 may contain segregations other than those containing a Ca-Sr-Mn-Si-based component as a main component. The total area of ​​the segregations in the cross section may be 100%, and the total area ratio of the segregations containing a Ca-Sr-Mn-Si-based component as a main component may be 50% or more.

[0064] The linear expansion coefficient of the segregations 23 a and 23 b may be smaller than the linear expansion coefficient of the dielectric particles 21 .

[0065] FIG. 3 is a schematic diagram of a dielectric having a special combination, and FIG. 4 is a schematic diagram of a dielectric not having the special combination.

[0066] Generally, when a dielectric having dielectric particles and segregation has a portion with a relatively large linear expansion coefficient, stress is applied from the portion with the large linear expansion coefficient to the portion with the small linear expansion coefficient, which may cause cracks in the dielectric.

[0067] In order to sinter the dielectric material at a low temperature, it is necessary to lower the sintering temperature by adding a sintering aid, but the addition of a sintering aid causes segregation with a small linear expansion coefficient.

[0068] In this case, compressive stress is applied from the dielectric particle 21 to the segregation 23b (not a special combination) as shown in Figure 4. The direction of the arrow indicates the direction of the stress, and the size of the arrow indicates the magnitude of the stress. The compressive stress makes the dielectric more susceptible to cracks.

[0069] Here, when the pores 25a are adjacent to the segregations 23a so as to have a special combination of the segregations 23a and the pores 25a as shown in Fig. 3, the compressive stress is alleviated. As a result, low-temperature sintering becomes easier and cracks are less likely to occur in the dielectric.

[0070] Next, an example of a method for manufacturing the multilayer ceramic capacitor 2 shown in FIG. 1 will be described.

[0071] First, a description will be given of the manufacturing process of the element body 4. In the manufacturing process of the element body 4, a dielectric paste that becomes the ceramic layers 10 after firing and an internal electrode paste that becomes the internal electrode layers 12 after firing are prepared.

[0072] The dielectric paste is manufactured using a powder containing a component that becomes a dielectric particle after firing (hereinafter, may be referred to as a dielectric powder) and a segregation powder containing a component that becomes a segregation after firing. Hereinafter, a case where the dielectric powder is made of a perovskite type compound and the segregation powder is made of a Ca-Sr-Mn-Si oxide will be described. However, there is no particular limitation on the composition of the dielectric powder and the composition of the segregation powder.

[0073] The dielectric powder can be manufactured by a solid-phase method, a hydrothermal synthesis method, a sol-gel method, etc. For example, in the solid-phase method, starting materials such as CaCO3 powder, SrCO3 powder, BaO powder, ZrO2 powder, and TiO2 powder are mixed uniformly by a means such as wet mixing, and then calcined to obtain a dielectric powder made of a perovskite compound. At this time, the calcined dielectric powder may be subjected to appropriate treatments such as pulverization and classification.

[0074] The segregated powder is obtained by mixing a compound powder containing Ca (e.g., CaCO3 powder), a compound powder containing Sr (e.g., SrCO3 powder), a compound powder containing Mn (e.g., MnCO3 powder), and a compound powder containing Si (e.g., SiO2 powder) in a predetermined ratio, followed by calcination. The composition of the segregation can be controlled by the compounding ratio of each compound powder, which is the starting material. In addition, when producing the segregated powder, a crushing process or the like may be appropriately performed to control the segregation diameter. Note that, as each compound powder, an oxide powder, a carbonate powder, a nitrate powder, a sulfate powder, or the like can be used, and it is sufficient to use a powder of a compound that becomes an oxide after firing.

[0075] The dielectric paste is obtained by adding the dielectric powder and the segregated powder to an organic vehicle and kneading them. The organic vehicle is a binder dissolved in an organic solvent. There is no particular limit to the type of binder. It may be appropriately selected from well-known binders such as polyvinyl butyral, acrylic, and ethyl cellulose. There is no particular limit to the type of organic solvent. It may be appropriately selected from well-known organic solvents such as methyl ethyl ketone, methanol, ethanol, acetone, toluene, terpineol, and butyl carbitol.

[0076] The dielectric paste is an organic paint. The dielectric paste may be an aqueous paint obtained by kneading a mixed powder with an aqueous vehicle. The aqueous vehicle is prepared by dissolving a water-soluble binder, a dispersant, etc. in water. There is no particular limitation on the type of water-soluble binder. It may be appropriately selected from well-known water-soluble binders such as polyvinyl alcohol, water-soluble acrylic resin, and water-soluble polyvinyl butyral resin.

[0077] By adjusting the compounding ratio of the dielectric powder and the segregation powder in the dielectric paste, it is possible to control the content ratio of segregation in the finally obtained ceramic layer 10. The dielectric paste may contain additives selected from various dispersants, plasticizers, dielectrics (other than perovskite type compounds), glass frits, etc., as necessary.

[0078] The internal electrode paste may be prepared by kneading a conductive material such as pure Ni powder or Ni alloy powder, an organometallic compound, and a resinate together with the organic vehicle described above. Instead of the conductive material, various oxides that become the above-mentioned Ni or Ni alloy after firing may be used. Furthermore, the dielectric powder contained in the dielectric paste may be added to the internal electrode paste as a co-material. The co-material has the effect of suppressing the sintering of the conductive powder during the firing process.

[0079] Next, the dielectric paste is formed into sheets by a doctor blade method or the like to obtain ceramic green sheets. Then, the internal electrode paste is applied in a predetermined pattern onto the ceramic green sheets by various printing methods such as screen printing or a transfer method. Furthermore, the green sheets on which the internal electrode patterns are formed are laminated in a plurality of layers, and then pressed in the lamination direction to obtain a mother laminate. At this time, the ceramic green sheets and the internal electrode patterns are laminated so that the ceramic green sheets are located on the upper and lower surfaces of the mother laminate in the lamination direction.

[0080] The mother laminate obtained by the above steps is cut into a predetermined size by dicing or pressing to obtain a plurality of green chips. The green chips may be solidified and dried to remove plasticizers, etc., as necessary.

[0081] The green chip may be barrel-polished using a horizontal centrifugal barrel machine, etc. When the green chip is subjected to solidification and drying, the green chip may be barrel-polished after solidification and drying.

[0082] In barrel polishing, the green chip is placed in a barrel container along with media and polishing liquid. The barrel container is rotated and vibrated to perform barrel polishing on the green chip. Barrel polishing removes unnecessary areas such as burrs that arise during cutting, and forms rounded corners (corner R) on the green chip. After barrel polishing, the green chip is washed with a cleaning liquid such as water and dried. This barrel polishing may also be performed after firing the green chip, which will be described later.

[0083] Next, the green chip obtained by the above method is subjected to a binder removal process and a firing process to obtain the element body 4.

[0084] The conditions for the binder removal process may be appropriately determined depending on the composition of the dielectric particles, the segregation composition, the composition of the internal electrode layer, etc. For example, the temperature increase rate may be 5 to 300°C / hour, the holding temperature may be 180 to 400°C, and the holding time may be 0.5 to 24 hours. The binder removal atmosphere may be air or a reducing atmosphere.

[0085] The firing conditions may be appropriately determined depending on the composition of the dielectric particles, the segregation composition, the composition of the internal electrode layer, and the like. For example, the holding temperature during firing may be 1200 to 1350°C, or 1220 to 1300°C. The holding time may be 0.5 to 8 hours, or 1 to 3 hours. The firing atmosphere may be a reducing atmosphere. For example, a humidified mixed gas of N2 and H2 may be used as the atmospheric gas. Furthermore, when the internal electrode layer is made of a base metal such as Ni or a Ni alloy, the oxygen partial pressure in the firing atmosphere may be set to 1.0×10-14 ~1.0×10 -10 It may also be expressed as MPa.

[0086] After the firing process, an annealing process may be performed as necessary. The annealing process is a process for reoxidizing the dielectric contained in the ceramic layer. When the firing process is performed in a reducing atmosphere, it is preferable to perform the annealing process. The conditions of the annealing process may be appropriately determined according to the composition of the dielectric particles, the composition of the segregation, the composition of the internal electrode layer, and the like. For example, the holding temperature may be 650 to 1150°C. The holding time may be 0 to 20 hours. The temperature increase rate and the temperature decrease rate may be 50 to 500°C / hour. The atmospheric gas may be dry N2 gas or humidified N2 gas. The annealing process may be performed multiple times.

[0087] In order to humidify the N2 gas or mixed gas in the above-mentioned binder removal treatment, firing treatment, and annealing treatment, for example, a wetter or the like may be used. When using a wetter, the water temperature may be about 5 to 75° C. Furthermore, the binder removal treatment, firing treatment, and annealing treatment may be performed consecutively or independently.

[0088] In each of the above heat treatments (binder removal treatment, firing treatment, and annealing treatment (reoxidation treatment)), the green chip is placed on a plate-shaped refractory setter and heated. After the heat treatment, the fired element body 4 is dropped from the setter and collected.

[0089] Next, a pair of external electrodes 6 are formed on the outer surface of the element body 4 obtained above. The method of forming the external electrodes 6 is not particularly limited. For example, when forming baked electrodes as the external electrodes 6, a conductive paste containing glass frit is applied to the end surface of the element body 4 by a dipping method, and then the element body 4 is heated at a predetermined temperature. When forming resin electrodes as the external electrodes 6, a conductive paste containing a thermosetting resin is applied to the end surface of the element body 4, and then the element body 4 is heated at a temperature at which the thermosetting resin hardens. Furthermore, after forming baked electrodes or resin electrodes by the above method, electrolytic plating, electroless plating, sputtering, vapor deposition, or the like may be performed to form the external electrodes 6 having a multilayer structure.

[0090] Through the above steps, a multilayer ceramic capacitor 2 having external electrodes 6 is obtained.

[0091] Three methods for producing the ceramic layer 10 including the dielectric material having a special combination will be described below. The method for producing the ceramic layer 10 including the dielectric material having a special combination is not limited to the following three methods.

[0092] (First production method) After the segregated powder is produced, a resin is applied to the segregated powder before the dielectric powder and the segregated powder are mixed together. There is no problem with the type of resin, so long as it is a resin that is insoluble or poorly soluble in organic solvents. Examples of resins that can be applied to the segregated powder include polyvinyl alcohol (PVA). PVA is a water-soluble resin that is insoluble in organic solvents.

[0093] The amount of the resin to be attached is not particularly limited, and may be 10 parts by mass or more and 100 parts by mass or less, based on 100 parts by mass of the segregation powder.

[0094] The process after the resin is attached to the segregated powder is as described above. During firing, the resin attached to the segregated powder disappears and becomes pores, resulting in a special combination.

[0095] (Second production method) After the segregation powder is produced, the segregation powder is mixed with carbon powder before the dielectric powder and the segregation powder are kneaded together. The amount of carbon powder to be mixed is not particularly limited. The amount of carbon powder may be 10 parts by mass or more and 100 parts by mass or less, assuming that the segregation powder is 100 parts by mass.

[0096] After mixing the segregation powder and the carbon powder, the process is as described above. During firing, the carbon powder disappears and becomes pores, resulting in a special combination.

[0097] (Third production method) A spray dryer is used when preparing the segregated powder. By using a spray dryer to prepare the segregated powder, at least a part of the obtained segregated powder has a hollow portion.

[0098] After the segregation powder with hollows is prepared, the process is as described above. During sintering, the hollows become pores and a special combination is created.

[0099] Although an embodiment of the present invention has been described above, the present invention is not limited to the above-described embodiment, and various modifications can be made without departing from the spirit of the present invention.

[0100] For example, in this embodiment, the multilayer ceramic capacitor 2 is exemplified as the multilayer electronic component, but the multilayer electronic component of the present invention may be a bandpass filter, a multilayer three-terminal filter, a thermistor, a varistor, or the like.

[0101] In this embodiment, the ceramic layers 10 and the internal electrode layers 12 are stacked in the Z-axis direction, but the stacking direction may be the X-axis direction or the Y-axis direction. In that case, the external electrode 6 may be formed to match the exposed surface of the internal electrode layer 12. The internal electrode layer 12 may be led out to the outer surface of the element body 4 via a through-hole electrode. In that case, the through-hole electrode and the external electrode 6 are electrically connected. EXAMPLES

[0102] The present invention will now be described in more detail with reference to examples, but the present invention is not limited to these examples.

[0103] (Experimental Example 1) Each capacitor sample shown in Table 1 below was fabricated according to the following procedure.

[0104] First, a dielectric powder, which is a raw material for the dielectric paste, and a segregation powder were prepared.

[0105] By solid phase method (Ca 0.70 Sr 0.30 )(Zr 0.96 Ti 0.04 )O3 powder was prepared. 0.70 Sr 0.30 )(Zr 0.96 Ti 0.04 )O3 powder is designated as powder A.

[0106] In Experimental Example 1, Powder A was used as the dielectric powder. The above composition is described in terms of atomic ratio. The composition of Powder A was common to all Examples and Comparative Examples, but the particle size of Powder A was set so that the average particle size of the dielectric particles in the final dielectric would be the value shown in Table 1.

[0107] In addition, CaCO3 powder, SrCO3 powder, MnCO3 powder, and SiO2 powder were wet mixed in a predetermined ratio, calcined, and then pulverized in a ball mill to prepare a segregated powder. In Example 1, powder made of Ca-Sr-Mn-Si oxide was used as the segregated powder. The particle size of the segregated powder was set so that the average diameter ratio described later would be the value shown in Table 1.

[0108] In the segregation contained in the finally obtained dielectric, the elements contained most abundantly on the basis of atomic number other than O, Ca, Sr, Zr, and Ti were set to be the elements shown in Table 1. All of the segregation powders used to prepare the samples other than Samples 14 and 15 had the same composition.

[0109] The segregation powders used to prepare the samples other than Samples 14 and 15 were prepared so that the molar ratio of CaCO3 powder, SrCO3 powder, MnCO3 powder, and SiO2 powder was Ca:Sr:Mn:Si=0.86:0.57:0.57:1.00. The segregation powders used to prepare Sample 14 were prepared so that the molar ratio of MnCO3 powder and MgCO3 powder was Mn:Mg=0.40:0.60. The segregation powders used to prepare Sample 15 were prepared so that the molar ratio of CaCO3 powder, SrCO3 powder, Al2O3 powder, and SiO2 powder was Ca:Sr:Al:Si=1.6:0.4:2.0:1.0.

[0110] Next, 35.75 parts by mass of the dielectric powder, 0.50 parts by mass of the segregation powder, 0.25 parts by mass of PVA, and 63.50 parts by mass of the organic vehicle were kneaded together to obtain a dielectric paste.

[0111] Separately, 50.63 parts by mass of Ni powder, 10.12 parts by mass of dielectric powder, and 39.25 parts by mass of an organic vehicle were kneaded together to obtain a paste for internal electrodes.

[0112] As the organic vehicle, ethyl cellulose was used.

[0113] Next, a green chip was manufactured by the sheet method using the dielectric paste and the internal electrode paste. The green chip was then subjected to binder removal, firing, and annealing to obtain an element body 4 (capacitor sample) with dimensions L0×W0×T0=3.2mm×2.5mm×2.5mm. In the obtained element body 4, the number of layers of the ceramic layer 10 sandwiched between the internal electrode layers 12 was 150, the average thickness of the ceramic layer 10 was 12μm, and the average thickness of the internal electrode layers 12 was 1.4μm.

[0114] The debindering treatment was performed at 260°C for 8 hours. The firing treatment was performed at 1240°C for 2 hours. The annealing treatment was performed at 750°C for 2 hours.

[0115] In sample number 1, no segregated powder and PVA were used. In sample number 2, no PVA was used. In sample number 3, no segregated powder was used. In sample number 4, the dielectric powder, the segregated powder, and the organic vehicle were mixed, and then the PVA was added. In sample numbers 5 to 19, a part or all of the PVA was attached to the segregated powder, and then the dielectric powder, the segregated powder, and the organic vehicle were mixed, and then the PVA that was not attached to the segregated powder was added. In order to control the number ratio of the special combination to the value shown in Table 1, the ratio of the amount of PVA attached to the segregated powder and the amount of PVA not attached to the segregated powder was controlled.

[0116] Each capacitor sample of Experimental Example 1 was subjected to the following evaluations.

[0117] The segregation phases present in the ceramic layer were analyzed by STEM-EDS.

[0118] First, a thin sample was taken from the ceramic layer 10 located near the center of the element body by a microsampling method using a focused ion beam (FIB) (JEOL JIB-4700F). Specifically, the ceramic layer 10 was roughly scraped at 30 kV-0.3 nA, and then processed into a thin sample of about 12 μm × 10 μm × 100 nm at 30 kV-100 pA. Note that cross-section cleaning was performed at 5 kV-70 pA.

[0119] Next, the cross section of the thin sample was observed using STEM-EDS (JEM-2200FS (HR) manufactured by JEOL Ltd.). For the observation of STEM-DF images, the observation magnification was 50,000 times and the acceleration voltage was 200 kV. For element mapping, the PHA was set to T2, the count rate was set to about 15,000 to 25,000 cps, the live time was set to about 1,500 seconds, the number of pixels was set to 256 × 256, and the sweep count was set to 200.

[0120] The size of the observation area of ​​the STEM image was 10 μm x 10 μm per location, and observations were performed at four different locations. Using the STEM-DF images and element mapping at the four locations, the presence or absence of segregation, the presence or absence of pores, and the presence or absence of special combinations were confirmed, and the percentage of the number of special combinations was calculated. In addition, the type of element that was most abundant in the segregation (most abundant segregating element) was confirmed, based on the atomic number, other than O, Ca, Sr, Zr, and Ti.

[0121] In addition, when it was difficult to judge whether segregation and pores were in contact with each other at a certain point, the surrounding area of ​​the point was enlarged until the observation area was 2 μm × 2 μm in size, and the segregation and pores were judged to be in contact if they were in contact with each other by even one dot, and not in contact with each other if they were not in contact by even one dot.

[0122] The average diameter of the segregation and the average diameter of the pores were calculated, and the value (average diameter ratio) was calculated by dividing the average diameter of the segregation by the average diameter of the pores. Furthermore, the average particle diameter of the dielectric particles (dielectric particle diameter) was calculated.

[0123] In all the examples and comparative examples, it was confirmed that the pore diameter of the special combination was smaller than the segregation diameter of the special combination.

[0124] The specific resistance (IR) of each sample was measured by measuring the insulation resistance at a reference temperature (25°C) using a digital resistance meter (R8340 manufactured by ADVANTEST). The specific resistance (IR) was calculated from the obtained insulation resistance, the effective electrode area, and the thickness of the dielectric. The results are shown in Table 1. The IR was 1.00×10 11 Ω or more is considered good, and 1.00×10 13 Ω or more was considered to be even better. The IR of sample number 5 is listed as 1.82E+13 in Table 1. This is 1.82×10 13 This means that.

[0125] In Experiment 1, the resistivity was 1.00×10 11 When the resistance was less than Ω, the crack occurrence rate was not evaluated.

[0126] Resistivity is 1.00×10 11 The crack occurrence rate was evaluated for each sample having a crack occurrence rate of 100 pieces for each sample number. Next, it was confirmed whether or not cracks existed in the dielectric of the prepared capacitor sample. Next, PCT (Pressure Cooker Test) was performed on the prepared capacitor sample. The PCT conditions were 121°C and 95% RH. It was confirmed whether or not cracks existed in the dielectric of the capacitor sample after 24 hours of PCT. Finally, the PCT was further performed on the capacitor sample after 24 hours of PCT, so that the total time of PCT was 168 hours. It was confirmed whether or not cracks existed in the dielectric of the capacitor sample after 168 hours of PCT. The results are shown in Table 1.

[0127] Capacitor samples before PCT were rated as good if the crack occurrence rate was 1% or less, i.e., 1 or less capacitor samples had cracks. Capacitor samples after 24 hours of PCT were rated as good if the crack occurrence rate was 10% or less, i.e., 10 or less capacitor samples had cracks. Capacitor samples after 168 hours of PCT were rated as good if the crack occurrence rate was 40% or less, i.e., 40 or less capacitor samples had cracks.

[0128] A case in which the crack occurrence rate was less than 1% all before the PCT, after the 24-hour PCT, and after the 168-hour PCT, in other words, no cracks were generated in any of the capacitor samples, was considered to be even better.

[0129] It was confirmed that the linear expansion coefficient of the segregation was smaller than that of the dielectric particles in all the examples and comparative examples. First, a sintered body was produced using only the above-mentioned dielectric powder. The sintered body produced using only the dielectric powder has the same composition as the above-mentioned dielectric particles. Separately, a sintered body having the same composition as the composition of the segregation phase was produced. Then, the average linear expansion coefficient of each sintered body was measured and confirmed. The average linear expansion coefficient of each sintered body was measured in the range from room temperature to 1200°C using thermomechanical analysis (TMA).

[0130] [Table 1]

[0131] As shown in Table 1, the capacitor samples with each sample number containing a dielectric material with a special combination had a high specific resistance IR. Also, compared with the capacitor samples with sample numbers 2 and 4, which had the same or higher specific resistance IR but contained a dielectric material without the special combination, they were significantly less likely to crack.

[0132] (Experimental Example 2) Experimental Example 2 was carried out under the same conditions as Sample Nos. 5 and 16 to 19 in Experimental Example 1 (Sample Nos. 20 to 24), except that the dielectric powder was barium titanate (Powder B). The results are shown in Tables 2 and 3. Note that when Powder B is used, the IR changes significantly compared to when Powder A is used, so the IR is not shown in Tables 2 and 3. However, it was confirmed that the IR of Sample Nos. 20 to 24 was approximately the same.

[0133] [Table 2]

[0134] [Table 3]

[0135] As can be seen from Tables 2 and 3, even if the composition of the dielectric powder, i.e., the composition of the dielectric particles, was changed, the capacitor samples containing the dielectrics having the special combination were significantly less susceptible to cracking.

[0136] 2. Multilayer ceramic capacitors 4 … Element body 4a … End face 4b…side 10 … ceramic layer 12 … Internal electrode layer 21...Dielectric particles 23a … (Special combination) segregation 23b … (non-special combination) Segregation 25a … (special combination) Pore 6 … External electrode

Claims

1. Contains dielectric particles, segregations, and pores; A dielectric material having a special combination in which the segregation and the pore are in contact with each other in a cross section.

2. The dielectric material according to claim 1 , wherein the diameter of the pores in the special combination is smaller than the diameter of the segregation in the special combination.

3. 3. The dielectric material according to claim 1, wherein a value obtained by dividing the average diameter of the segregations by the average diameter of the pores is greater than 1.00 and equal to or less than 6.

00.

4. The ratio of the number of the special combinations in the cross section of the dielectric is 2.0×10 4 pieces / mm 2 That's it, 5.0 x 10 6 pieces / mm 2 3. The dielectric material according to claim 1 or 2, wherein:

5. 3. The dielectric material according to claim 1, wherein the segregation has a linear expansion coefficient smaller than that of the dielectric particles.

6. 3. The dielectric material according to claim 1, wherein an element contained in the segregation in the greatest amount in terms of atomic number other than O, Ca, Sr, Zr and Ti is Si.

7. 3. The dielectric material according to claim 1, wherein the particle diameter of the dielectric particles is 0.10 μm or more and 3.00 μm or less.

8. The dielectric particles have the composition formula [(Ca x Sr 1-x ) O] n [(Ti y Zr 1-y ) O 2 3. The dielectric material according to claim 1, comprising a component represented by the formula:

9. The dielectric material according to claim 1 or 2, wherein the dielectric particles comprise barium titanate.

10. A laminated electronic component comprising the dielectric material according to claim 1 or 2.

Citation Information

Patent Citations

  • Multilayer ceramic capacitor

    JP2004273975A